Antioxidant Activity of Various Plant Extracts Assessed Using the ABTS Method - Radiartini, Ni Nyoman; Andayani, Yayuk (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Free radicals are unpaired electrons, making them highly reactive and unstable, with the potential to damage body cells and trigger various diseases. To prevent the adverse effects caused by free radicals, the body requires protection from antioxidant compounds. Numerous studies have confirmed that certain types of plants possess antioxidant activity, tested using the ABTS method. This review article aims to identify plant extracts with antioxidant activity based on the ABTS method. The method used was a literature study, focusing on journal searches on the Google Scholar platform using relevant keywords and concentrating on publications from the past ten years. The review results indicate that extracts from different plant parts show varying levels of antioxidant activity, ranging from very strong to moderate, supported by different IC50 values.